Minerais potássicos, acidificados ou não, utilizados como fontes de nutriente para o milho (Zea mays L) em casa de vegetação: I- peso da parte aérea, das raízes e do total - Dutra, Leôncio G; Lima Thiébaut, José Tarcísio; Domingos Fabris , José (Revista Ceres, 2025)
The effects of potassium minerals were studied as these influenced the production of dry matter of corn. Biotiteand leucite, with partial acidification, and carnalite, without acidification, were employed with potassium chloride used for comparison.